Functional validation of the albinism-associated tyrosinase T373K SNP by CRISPR/Cas9-mediated homology-directed repair (HDR) in rabbitsResearch in context - Yuning Song; Yuxin Zhang; Mao Chen; Jichao Deng; Tingting Sui; Liangxue Lai; Zhanjun Li (EBioMedicine, 2018)
Background: Oculocutaneous albinism (OCA) is a group of autosomal recessive disorders characterized by reduced melanin that are caused by mutations in the gene encoding tyrosinase (TYR), which is the rate-limiting enzyme in the production of the pigment melanin. Many studies or meta-analyses have suggested an association between the TYR T373K SNP and OCA1, but there is limited biochemical and genetic evidence to support this association. Methods: We overexpressed TYR-WT and TYR-T373K mutants on HK293T cells and tested the changes of melanin production and tyrosinase activity. Then we generated TYR-K373T knock-in (KI) rabbits by microinjection of ssDNA and synthesized RNAs targeting C1118A using CRISPR/Cas9-HDR to observe the formation of melanin. Findings: We demonstrated that the T373K mutation in TYR can reduce tyrosinase activity, leading to an absence of melanin synthesis at the cell-level. The gene-edited TYR-K373T rabbits exhibited rescued melanin production in hair follicles and irises, as inferred from the evident decrease in pigmentation in TYR-T373K rabbits, thus providing functional validation of the albinism-associated T373K SNP at the animal level. Interpretation: Our study provides the first animal-level functional validation of the albinism-associated TYR K373T SNP in rabbits, and these results will facilitate gene therapy of OCA1 in pre-clinical settings in the future. Fund: The National Key Research and Development Program of China Stem Cell and Translational Research, the Strategic Priority Research Program of the Chinese Academy of Sciences, the Guangdong Province Science and Technology Plan Project, and the Program for JLU Science and Technology Innovative Research Team. Keywords: Tyrosinase, OCA, T373K, Point mutation, Rabbit, CRISPR/Cas9